Periodic limb movements during sleep in stroke/TIA: Prevalence, course, and cardiovascular burden - Manconi, Mauro (Neurology, 2018)
OBJECTIVE: To define the prevalence, time course, and associated factors of periodic limb movements during sleep (PLMS) in patients with ischemic stroke or TIA. METHODS: Patients enrolled in the prospective Sleep-Disordered Breathing in Transient Ischemia Attack (TIA)/Ischemic Stroke and Continuous Positive Airway Pressure (CPAP) Treatment Efficacy (SAS-CARE) study underwent a double polysomnographic investigation in the acute and chronic phases after stroke/TIA, together with a MRI brain scan and a 24-hour blood pressure evaluation. The prevalence of PLMS in patients was compared with that in a matched sample of randomly selected healthy controls from the HypnoLaus cohort. One hundred sixty-nine recordings were performed in the acute phase and 191 after 3 months (210 recordings were obtained from the same 105 patients in both phases) and were compared to those of 162 controls. RESULTS: The mean number of PLMS per hour and the percentage of participants with a PLMS index >10 and >15 per hour were similar between patients and controls. PLMS remained stable from the acute to the chronic phase after stroke. Factors positively associated with PLMS were age, body mass index, and history of hypertension. Blood pressure over 24 hours and the burden of cerebrovascular damage were similar between the groups with PLMS and without PLMS. CONCLUSIONS: PLMS are equally frequent in patients with stroke/TIA and the general population. The absence of higher blood pressure values and of a greater vascular brain damage found in patients with PLMS compared to those without PLMS might be due to a greater use of antihypertensive medication among patients with PLMS, which corresponds to a higher prevalence of previous diagnosis of hypertension in these patients.